STUDI TENTANG DETERMINAN ACTUAL PURCHASE BEHAVIOR PADA RESTORAN: PENGUJIAN ATAS PERCEIVED FOOD QUALITY, PERCEIVED PRICE, DAN RESTAURANT TRUST - Ari Setiyaningrum; Lina Salim (STIE Pelita Nusantara Semarang, 2021)
This study aims to examine a model of the determinants of actual purchase behavior in the context of the restaurant industry. This research specifically examines whether perceived food quality and perceived price have a direct or indirect effect on actual purchase behavior through restaurant trust as a mediating variable in the context of the restaurant industry. Data collection was carried out using an online survey involving 295 respondents who had read online reviews about the restaurants they would visit on the Zomato, Gokuliner, Food Advisor, and Trip Advisor applications. Research data were analyzed using PLS-SEM with smartPLS software. The results of the study found that perceived food quality and perceived price had a direct influence on actual purchase behavior. The study also found that perceived food quality and perceived price have a positive effect on restaurant trust. The results of the mediation test found that restaurant trust was proven to mediate the effect of perceived food quality on actual purchase behavior, but restaurant trust was not proven to mediate the effect of perceived price on actual purchase behavior.